(untitled) (Indian Journal of Arid Horticulture, 2025)
The field experiment was conducted during Kharif 2014 on seasonal incidence of chilli thrips (Scirtothrips dorsalis Hood) and its natural enemies. The results revealed that the higher population of thrips and coccinillids was recorded in the range of 11.27 to 14.93 thrips per 6 leaves per plant and 0.40 to 0.53 coccinillids per plant, respectively during 2nd week of October to 1" week of November. However, peak activity of thrips (14.93 per 6 leaves per plant) and cocinillids (0.53 per plant) was observed during the 4* week of October (44" MW) and 1 week of November (45" MW). Then gradually declined in population up to last week of December (52 MW). All the weather parameters i.e. temperatures (maximum and minimum), relative humidity (morning and evening) and rainfall were correlated negatively with the incidence of thrips population and abundance of coccinellids except maximum temperature showed positive correlation with coccinellids.